Influence of managers' empathic skills on school success - Toeremen, Fatih; Ekinci, Abdurrahman; Karakus, Mehmet (Emerald Group Publishing Ltd, 2006)
Purpose - The main purpose of this investigation is to find out the influence of empathic skills of managers on the success of schools. Design/methodology/approach - In this study, survey based descriptive scanning model was used. This study was fulfilled in Batman city on teachers working at public and private primary schools in 2003-2004 education year. According to the results of the central evaluation examination, schools were divided into three success groups (each group having seven schools). About 10 teachers were randomly selected from each of these schools, and then the 23 itemed questionnaire was administered. Findings - As a result of the research it was seen that empathic skills of managers and school success had a very close relationship. There were meaningful differences between the first group and the other two groups. Successful schools' managers clearly had better empathic skills and unsuccessful schools' managers had little empathic skills. The same situation was seen between the second group and the third group as well. Research limitations/implications - The results of this research may be affected by local conditions in which it was conducted. Practical implications - The empathic skills which are revealed as important indicators of success should be taken into consideration during the selection and training of managers. Originality/value - This paper discusses the empathic aspect of school management which has been rarely taken up and displays the importance of empathic skills on school success.
Keywords: Managers; Skills; Schools; Critical success factors